Checking out with the Payment Request API : a practical introduction to the HTML5 Payment Request API using real-world examples - Libby, Alex (Apress, 2019)
Quickly create consistent checkouts for use within websites, using the power of the HTML5 Payment Request API. This project-oriented book simplifies the process of creating and manipulating checkouts with the Payment Request API in browsers for websites or online applications, using little more than a text editor or free software. One of the key concerns of any e-commerce company is ensuring customers complete the checkout process successfully, and for them to return. Unfortunately, many checkouts still suffer from a high level of drop-out. The Payment Request API is an open standard being developed by browser vendors to simplify payments for users with a quick and seamless autofill process enabling a broader set of online payment providers to participate in the market. The API is designed to be easy to implement across all supported browsers, and work with any payment type or service provider. Checking Out with the Payment Request API equips you with a tool set that you can use to develop future projects, incorporate into your existing workflow and allow you to reduce any dependency on complex, custom-made checkouts that might be prone to failure, or unwieldy to use. You'll learn how to use the Payment Request API to create consistent checkouts quickly and easily, and work through practical example projects that will help familiarize you with using the API. We live in an age where speed and accuracy are of the essence - add effortless flow to your payments using this book today. What You'll Learn Implement the Payment Request API in a project Explore some of the options for personalizing it for a project Gain an appreciation of pointers around user experience and how this affects the API Understand how to manage issues and security when using the Payment Request API Work through some example projects, from standalone demos to implementing in frameworks Who This Book Is For Website developers familiar with creating shopping carts and looking to leverage the HTML5 Payment Request API. Also ideal for those in agile development teams who want to focus on simplifying content in modern browsers using their existing tools.